2013
DOI: 10.1089/ten.tea.2012.0384
|View full text |Cite
|
Sign up to set email alerts
|

Genipin-Crosslinked Cartilage-Derived Matrix as a Scaffold for Human Adipose-Derived Stem Cell Chondrogenesis

Abstract: Autologous cell-based tissue engineering using three-dimensional scaffolds holds much promise for the repair of cartilage defects. Previously, we reported on the development of a porous scaffold derived solely from native articular cartilage, which can induce human adipose-derived stem cells (ASCs) to differentiate into a chondrogenic phenotype without exogenous growth factors. However, this ASC-seeded cartilage-derived matrix (CDM) contracts over time in culture, which may limit certain clinical applications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
116
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 61 publications
11
116
4
Order By: Relevance
“…Cheng et al showed acellular porcine cartilage-derived matrix was able to support the growth of neocartilage formation in the absence of exogenous growth factors [143]. Recently the same group was able to induce chondrogenic differentiation of human adipose-derived stem cells without exogenous growth factors on an acelluar cartilage matrix crosslinked with genipin to prevent scaffold contraction [145].Schwarz et al have shown the successful decellularisation and sterilization of porcine knee and nasal cartilage and human nasal cartilage. They also show the ability to remove proteoglycan content whilst maintaining the collagen structure.…”
Section: Acellular Biological Scaffoldsmentioning
confidence: 99%
“…Cheng et al showed acellular porcine cartilage-derived matrix was able to support the growth of neocartilage formation in the absence of exogenous growth factors [143]. Recently the same group was able to induce chondrogenic differentiation of human adipose-derived stem cells without exogenous growth factors on an acelluar cartilage matrix crosslinked with genipin to prevent scaffold contraction [145].Schwarz et al have shown the successful decellularisation and sterilization of porcine knee and nasal cartilage and human nasal cartilage. They also show the ability to remove proteoglycan content whilst maintaining the collagen structure.…”
Section: Acellular Biological Scaffoldsmentioning
confidence: 99%
“…heart valves, blood vessels, skin and cartilage [8,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]) scaffolds. In the case of articular cartilage, numerous studies have demonstrated that scaffolds derived from devitalized cartilage are chondroinductive and show great promise for regenerating damaged joints [8,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that may limit ECM derived scaffolds for cartilage tissue engineering applications is cell-mediated contraction of the construct either during in vitro culture or following implantation into a defect [44]. To overcome such problems different crosslinking techniques can be used to minimise or prevent contraction such as dehydrothermal (DHT) [28,42,[48][49][50][51][52][53][54][55], UV light [42,50] and chemical crosslinking [42,54,56,57]. Chemical methods include the use of glutaraldehyde [54,[58][59][60], 1-Ethyl-3-3dimethyl aminopropyl carbodiimide (EDAC) [42,49,54,61,62] and genipin [57].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations